Testicular extracellular matrix/gelatin-based scaffold using gas foaming to support spermatogonial stem cells - Maryam Momeni; Mohammad Kazemi Ashtiani; Zahra Bashiri; Zohreh Bagher; Hamid Reza Asgari; Morteza Koruji (Iranian Journal of Basic Medical Sciences)
Objective(s): Developing a bioactive testicular scaffold has been proposed as a potential option to preserve male fertility. Using the gas foaming method, this study aimed to fabricate an effective and highly porous scaffold derived from a gelatin-testicular extracellular matrix. Materials and Methods: Male ram testis decellularization was performed using a combination of NaCl buffer and Triton. Then, evaluations were done for 4′,6-diamidino-2-phenylindole, hematoxylin-eosin staining, and quantitative DNA content. Masson’s trichrome, Alcian blue, and orcein staining were conducted to ensure the maintenance of ECM components post-decellularization. Porous scaffolds were fabricated using gelatin incorporation with various concentrations of extracted ECM via the gas foaming method. The mechanical and structural characteristics of the scaffolds, along with evaluations of cell spreading and penetration depth, were performed. Furthermore, scaffolds were used to culture mouse spermatogonial stem cells to investigate the morphology, viability, and adhesion of the cells on the scaffolds.Results: Our results showed successful decellularization of testicular tissue, resulting in significant removal of DNA content while preserving ECM major components. The hybrid scaffolds exhibited uniform porous microstructures with a pore size average ranging from 298-330 μm. There were no significant differences in biodegradation and swelling ratios between the scaffolds. The cell penetration index significantly increased in gel-ECM by 5% compared to other groups. Also, ECM5% led to increased cell attachment and viability, proper compressive strength, and a decrease in Young’s module. Conclusion: Our study suggests that using a combination of testicular ECM and gelatin shows promise in constructing bioartificial testes through the gas-foaming method.